Small Bowel Review: Part II - ABR Thomson; M Keelan; A Thiesen; MT Clandinin; MJ Ropeleski; G Wild (Canadian Journal of Gastroenterology)
In the past year, there have been many advances in the area of small bowel physiology and pathology. In preparation for this review, over 1500 papers were assessed. Some have been selected and reviewed, with a particular focus on presenting clinically useful information for the practising gastroenterologist. Relevant review articles have been highlighted, and important clinical learning points have been stressed. The topics are varied in scope and wherever possible show a logical progression from basic physiology to pathophysiology to clinical disorders and management.